TRUCKS AS INSPIRATION FOR BABY BED CREATION - Agus Triana; Sri Marwati (Institut Seni Indonesia Surakarta, 2020)
Baby bed is one type of furniture which the existence is very necessary to meet the needs of the community, especially in family groups who have children / babies. The idea of creating the work is divided into two problem formulations, namely, how to design a baby bed in the form of a truck with decorative elements of Punakawan and how to visualize the design into works of art. The approach used is Dewitt H. Parker's aesthetic theory. The method of creation includes 3 stages, namely: the exploration stage, the design stage, and the embodiment stage. The baby bed produced in this artistic research is a work that has functional and aesthetic values with reference to the character of Punakawan. The symbolic value contains the exemplary teachings of Punakawan become a substance in this baby bed artwork. These baby beds are created creatively and innovatively for the renewal of baby bed shapes.